SELF-ESTEEM, CREATIVE THINKING, AND ATTITUDES IN TECHNICAL EDUCATION: IMPLICATION FOR THE DEVELOPMENT OF TVET IN NIGERIA - Isaac Ikorogbudu, Walter (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The educational system in Nigeria has witnessed increased development in technical and vocational training. Intimations suggest that enrollment in the TVET programs are beyond expectation. However, many authors have underscored various factors influencing students' perception of TVET. Little is known about the role of self-esteem and creative thinking in attitudes relating to TVET in Nigeria. The present study investigated secondary school students' attitudes toward TVE based on creative thinking and self-esteem. One hundred and sixty-six secondary school students drawn from public and private secondary schools in River State participated in the study. The participants completed self-report measures on attitude towards TVE, creative thinking assessment, and Rosenberg's self-esteem scale. The findings revealed that 65.5% of the respondents expressed a positive attitude toward TVE. Also, a multiple regression model was computed to test the study's hypothesis. The results showed that creative thinking and self-esteem positively correlated with attitudes toward TVE (r = 0.47, F = 41.13, p<0.01). Notably, creative thinking and self-esteem explained about 21.2% of the variation in attitudes towards TVE. The findings and practical implications of the study are discussed.